Antiviral activity of fermented foods and their probiotics bacteria towards respiratory and alimentary tracts viruses. (September 2021) - Muhialdin, Belal J.; Zawawi, Norhasnida; Abdull Razis, Ahmad Faizal; Bakar, Jamilah; Zarei, Mohammad
Abstract: The recent COVID-19, a viral outbreak calls for a high demand for non-conventional antiviral agents that can reduce the risk of infections and promote fast recovery. Fermented foods and their probiotics bacteria have recently received increasing interest due to the reported potential of high antiviral activity. Several probiotics strains demonstrated broad range of antiviral activities and different mechanisms of action. This article will review the diversity, health benefits, interaction with immune system and antiviral activity of fermented foods and their probiotics bacteria. In addition, the mechanisms of action will be reviewed to determine the broad range potential antiviral activity against the respiratory and alimentary tracts viruses. The probiotics bacteria and bioactive compounds in fermented foods demonstrated antiviral activities against respiratory and alimentary tracts viruses. The mechanism of action was reported to be due to the stimulation of the immune system function via enhancing natural killers cell toxicity, enhance the production of pro-inflammatory cytokines, and increasing the cytotoxic of T lymphocytes (CD3 +, CD16 +, CD56 + ). However, further studies are highly recommended to determine the potential antiviral activity for traditional fermented foods. Highlights: This review highlights the diversity of fermented foods. Fermented foods contain probiotics bacteria and bioactive compounds. Fermented foods demonstrated broad range antiviral activity. The mechanisms of action are via the stimulation of the immune system function.